1996
DOI: 10.1073/pnas.93.21.11786
|View full text |Cite
|
Sign up to set email alerts
|

Major histocompatibility class I presentation of soluble antigen facilitated by Mycobacterium tuberculosis infection.

Abstract: Cell-mediated immune responses are essential for protection against many intracellular pathogens. For Mycobacterium tuberculosis (MTB), protection requires the activity of T cells that recognize antigens presented in the context of both major histocompatibility complex (MHC) class II and I molecules. Since MHC class I presentation generally requires antigen to be localized to the cytoplasmic compartment of antigen-presenting cells, it remains unclear how pathogens that reside primarily within endocytic vesicle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
109
2
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(119 citation statements)
references
References 34 publications
7
109
2
1
Order By: Relevance
“…Previous studies have provided evidence of a TAP-dependent pathway during mycobacterial infection. TAP-knockout mice have enhanced susceptibility to tuberculosis (28,62), and phagosomes in macrophages infected for 18 -36 h with live BCG show enhanced permeability to macromolecules (30,32). In contrast, the 19-kDa pathway identified in the present study belongs to the TAP-independent category and is novel in its dependence on acylation.…”
Section: Discussioncontrasting
confidence: 47%
“…Previous studies have provided evidence of a TAP-dependent pathway during mycobacterial infection. TAP-knockout mice have enhanced susceptibility to tuberculosis (28,62), and phagosomes in macrophages infected for 18 -36 h with live BCG show enhanced permeability to macromolecules (30,32). In contrast, the 19-kDa pathway identified in the present study belongs to the TAP-independent category and is novel in its dependence on acylation.…”
Section: Discussioncontrasting
confidence: 47%
“…Mycobacteria have evolved mechanisms to evade the phagolysosomal environment and probably escape to the cytoplasm [58]. Cytotoxic CD8 cells recognize the antigens when presented with major histocompatibility complex (MHC) class I molecules [6].…”
Section: Resultsmentioning
confidence: 99%
“…Other groups have shown that heat shock fusion proteins and soluble Ags from M. tuberculosis can be presented via the MHC class I pathway (54,55). However, the means by which Ags, from a bacteria which has been shown to reside within the phagosome (a site inaccessible to the MHC class I presentation pathway) are presented to CD8 ϩ T cells is unclear (56,57).…”
Section: Discussionmentioning
confidence: 99%